Characterization of skin microbiota in patients with atopic dermatitis and in normal subjects using 16S rRNA gene-based comprehensive analysis - Dekio, Itaru; Sakamoto, Mitsuo; Hayashi, Hidenori; Amagai, Masayuki; Suematsu, Makoto; Benno, Yoshimi (Journal of medical microbiology, 2007)
1 Department of Dermatology, School of Medicine, Keio University, Shinjuku-ku, Tokyo 160-8582, Japan 2 Microbe Division/Japan Collection of Microorganisms, RIKEN BioResource Center, Wako, Saitama 351-0198, Japan 3 Department of Biochemistry and Integrative Medical Biology, School of Medicine, Keio University, Shinjuku-ku, Tokyo 160-8582, Japan Correspondence Itaru Dekio dekio{at}1999.jukuin.keio.ac.jp Received 5 March 2007 Accepted 26 August 2007 A previous study using bacterial 16S rRNA gene-based clone libraries revealed that the microbiota in healthy human skin included uncultured micro-organisms, although the micro-organisms in skin exposed to disease conditions remain to be examined. To compare the profiles of skin microbiota in 13 patients with atopic dermatitis (AD) and 10 healthy controls, terminal RFLP analysis of bacterial 16S rRNA genes was applied to 23 swab-scrubbed samples from facial skin. This culture-independent analysis successfully revealed the complex bacterial members of the microbiota as peak patterns following capillary electrophoresis of terminal restriction fragments (T-RFs). Each T-RF peak reflected a micro-organism, and the micro-organism to which each peak was assigned could be identified by computer simulation of T-RF length using the nucleotide sequence data of bacterial species residing in the skin. Among 18 species detected in the study, Stenotrophomonas maltophilia was detected significantly more commonly in AD patients (5/13 for AD patients vs 0/10 for controls), whilst Dietzia maris was detected significantly more commonly in normal controls (8/10 for controls vs 2/13 for AD patients). Moreover, Streptococcus species, which are considered to be uncommon in uninfected skin, were detected in seven patients and eight normal controls. Although further studies should be undertaken to investigate the roles of these micro-organisms in AD, the microbiota were presumed to include hitherto uninvestigated bacterial species in the major population of patients with AD and of healthy controls. Abbreviations: AD, atopic dermatitis; T-RF, terminal restriction fragment; T-RFLP, terminal RFLP. Present address: Faculty of Engineering, Maebashi Institute of Technology, Kamisatori-Machi, Maebashi, Gunma 371-0816, Japan. The GenBank/EMBL/DDBJ accession numbers for the 16S rRNA gene sequences obtained from clone libraries are AB264551–AB264556.